Penerapan Metode EOQ (Economic Order Quantity) untuk Meningkatkan Efisiensi Pengendalian Persediaan Bahan Baku di Kelana Roaster - Adhim, Muhammad Arsil; Zahra, Alyana Mevia; Setiawan, Aulia Nursyifa; Rukmana, Faryal Virgiana Cikal; Pasaribu, Lasma Rintan Antonia (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
Kelana Roaster is a coffee bean supplier that produces roasted coffee beans and sells flavored syrup which has become a coffee provider for 30 coffee shops spread across Bogor City. In order to maintain a safe supply of coffee beans, Kelana Roaster receives supplies of raw coffee beans from farmers in 3 regions, including Garut, Temanggung, and Aceh. The problem faced by Kelana Roaster is the uncertainty of order quantities at certain times so that ordering costs often experience spikes, causing a decrease in profits of 11,877%. This study aims to solve the problem of raw material inventory management at Kelana Roaster through the application of EOQ (Economic Order Quantity). The research method used in this research is a quantitative method with a comparative approach that compares the calculation using ordering costs using the EOQ method with the calculation of ordering costs before EOQ. The results obtained through the application of the EOQ (Economic Order Quantity) method are the total inventory cost of Rp 3,035,645 with an ordering cycle of 2 times per year. This figure shows a savings of 31.936% compared to the calculation of inventory costs previously carried out by Kelana Roaster.